The incredible boong gi: Educational game RPG for mathematical understanding ability - Setiyani Setiyani; Sri Sumarwati; Laela Sagita; Dzaki Fadhlurrohman (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
Some of the android-based mobile game genres that are currently very popular such as adventure, first-person shooter, fighting, racing, and others. This development should provide opportunities in the field of education to make games not only for fun but also for education. The purpose of this study was to produce educational games that were valid, practical, and had potential effects to improve the mathematical understanding of the relationship and function of junior high school students. The research method used is RD (research development) using the ADDIE model. The data collection techniques used were documentation, interviews, and tests of mathematical comprehension abilities. The results obtained from the game